Metaphors in anti-bias educational program: Educators' voices [Eğitimcilerin gözünden ayrimcilik karşiti eğitim programi'na ilişkin bir metafor çalişmasi] - Koşan, Y.; Kuru, N.; Korkmaz, A.; Karademir, A.; Akman,B. (Pegem Akademi Yayincilik Egitim Danismanlik Hizmetleri, 2018)
The purpose of this research is to review the perceptions of faculty members, preschool teachers, and pre-school teacher candidates with regard to the Anti-Bias Education Programs (ABEP) by using a phenomenological pattern. The participants' metaphors on ABEP were established and categorized and the differences in participants' perceptions were analyzed in terms of their demographic characteristics such as age, gender, and service time. The working group of this research consisted of 129 participants: from 17 universities, 22 faculty members from the Education Faculty Pre-school Education Departments and 71 pre-school teacher candidates, studying in the fourth year of the Pre-School Education Departments; and 36 pre-school teachers from 9 different cities. The findings of this study show that faculty members produced 17, teachers produced 28 and teacher candidates produced 30 different metaphors about ABEP. The faculty members' metaphors vary in terms of age and service time, whereas the teachers' vary in terms of service time, type of institution, education level and age. Teacher candidates' metaphors vary in terms of age and gender. © 2018 Pegem Eğitim ve Öğretim Dergisi.
Keywords: Anti bias education program; Educators; Metaphor